2004
DOI: 10.1111/j.1365-2036.2004.02297.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trends in ulcer diagnosis in a population with high prevalence of Helicobacter pylori infection

Abstract: SUMMARYBackground: It is unknown whether the incidence of peptic ulcer changes in areas with a high prevalence of Helicobacter pylori infection. Aim: To determine trends in peptic ulcer complications in a community with a high prevalence of H. pylori infection. Methods: New endoscopic diagnoses of peptic ulcers and their complications from 1985 to 2000 were obtained. H. pylori infection in the adult population, the number of prescriptions for anti-secretory drugs and non-steroidal anti-inflammatory drugs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
82
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 26 publications
5
82
1
3
Order By: Relevance
“…Our results confirmed those of other African authors including Millogo [6], Lawson [8], Diarra [7], and Diouf [11] with respectively 43.4, 43.56 years, 43.28 years and 42.5 years. The PUD occurs at a later age in the European than in African one [8].…”
Section: Demographic Aspectssupporting
confidence: 91%
See 2 more Smart Citations
“…Our results confirmed those of other African authors including Millogo [6], Lawson [8], Diarra [7], and Diouf [11] with respectively 43.4, 43.56 years, 43.28 years and 42.5 years. The PUD occurs at a later age in the European than in African one [8].…”
Section: Demographic Aspectssupporting
confidence: 91%
“…This was hematemesis associated to melena in five patients. Ibara [9] in Brazzaville and Lawson in Lome [8] found higher rates 18.14% and 20.51% respectively. This difference is probably due to the method of recruitment (endoscopic study).…”
Section: Clinical Aspectsmentioning
confidence: 87%
See 1 more Smart Citation
“…Durante os anos 80, a infecção pelo H. pylori foi demonstrada em mais de 90% dos pacientes com UD e em torno de 70% dos pacientes com UG (15,5) . O declínio na incidência e prevalência da úlcera péptica em países desenvolvidos tem ocorrido em paralelo à queda da prevalência da infecção gástrica pelo H. pylori, principalmente em populações com altas médias de infecção (16,28) . O uso de AINES, a despeito de seu bem determinado efeito analgésico e antiinflamatório, é provavelmente a causa mais comum de lesão da mucosa gastrointestinal em países do ocidente.…”
Section: Discussionunclassified
“…In Holland, a retrospective study of 14,909 endoscopies performed during 10 years (1993 to 2002) showed a trend towards decrease in infection prevalence in patients less than 50 years old, pointing to a lower than 10% prevalence in this age group in 2009 and global prevalence less than 10% in 2027 (8) . In Spain there was a reduction in prevalence from 1990 to 2000 (adults) among users of an endoscopy service from 76.3% to 69.3% with a parallel decrease in duodenal ulcer incidence (130.8 per 100,000 inhabitants in 1985 to 86.1 in 2000) and its complications (109.1 per 100,000 inhabitants in 1990 to 81.4 in 2000) (14) . In the period, in spite of the slight increase in antiinflammatory drug use, there was a great increase in the prescription of proton pump inhibitors.…”
Section: Discussionmentioning
confidence: 99%